Perceptions and characteristics of public space and urban environment among city inhabitans in Cúcuta-Colombia - Vergel-Ortega, Mawency; Contreras-Díaz, Margarita María; Martínez-Lozano, José Joaquín (Prospectiva. Revista de Trabajo Social e Intervención Social, 2016)
The objective of this article is to identify the perceptions about public space and environment of different actors in Cucuta city. The research flows a mix focus, descriptive and correlational type and content analysis from deep interviews of representative persons of five groups of social actors and application of VIDHA survey of city people. Results: the community considers of high importance the inclusion of citizenship in the city constructions, where the aesthetics will be present as renovate social element and sensorial link in security perception. Traffic jam y place signaling of abandoned place determines diminish of public space, relegated to functional compliance. Conclusion: Planning, respect for fundamentals urban standards, architecture, design in a cultural environment are associated factors to improvement; citizens, public space, environmental education, place are emergent categories; closed fractioning propitiated symbolic representations of security where the fear in relevant dimension.